2019
DOI: 10.1186/s12944-019-0962-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on Fetuin-a in obese, type 2 diabetes and cardiovascular disease in adults and elderly: a systematic review and Meta-analysis

Abstract: BackgroundElevated levels of fetuin-A are associated with increased risks of metabolic syndrome, type 2 diabetes and nonalcoholic fatty liver disease. This meta-analysis investigated whether exercise interventions can reduce fetuin-A in adults.MethodsWe searched clinical trials that objectively assessed fetuin-A and included study arms with exercise intervention. The pre-intervention and post-intervention data were used for meta-analysis. The effect sizes were calculated as standardized mean differences or cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
0
12
2
3
Order By: Relevance
“…This raised fetuin-A was not related to insulin sensitivity but was associated with VO2max (44). In a recently published systematic review and meta-analysis study in obese, T2D undergoing moderate to intense supervised exercise reported a reduction in fetuin-A following exercise (45). In our study cohort, 8 weeks of moderate intensity exercise did not have any significant effects on FGF19, FGF21, FGF23, and fetuin-A levels.…”
Section: Discussioncontrasting
confidence: 43%
“…This raised fetuin-A was not related to insulin sensitivity but was associated with VO2max (44). In a recently published systematic review and meta-analysis study in obese, T2D undergoing moderate to intense supervised exercise reported a reduction in fetuin-A following exercise (45). In our study cohort, 8 weeks of moderate intensity exercise did not have any significant effects on FGF19, FGF21, FGF23, and fetuin-A levels.…”
Section: Discussioncontrasting
confidence: 43%
“…Additionally, favorable changes in fetuin-A, liver fat and insulin sensitivity have also been reported following long-term (12 weeks) aerobic and resistance exercise training (Lee et al, 2017). A recent meta-analysis reported that both aerobic and resistance training significantly reduced fetuin-A in dysglycemic and overweight/obese individuals when performed at a moderate or vigorous intensity, with a volume of 60 min per session and a minimum frequency of 4-7 sessions per week (Ramírez-Vélez et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many published reviews have suggested that circulating fetuin-A may play a role in the risk of type 2 diabetes mellitus, cardiovascular disease, and nonalcoholic fatty liver disease [18,19]. For example, a meta-analysis on the association between type 2 diabetes mellitus and circulating fetuin-A showed that circulating fetuin-A concentrations in type 2 diabetes mellitus patients were significantly higher than in the controls [19].…”
Section: Discussionmentioning
confidence: 99%